Mechanisms of change in an emotion regulation group therapy for deliberate self-harm among women with borderline personality disorder. (February 2015) - Gratz, Kim L.; Bardeen, Joseph R.; Levy, Roy; Dixon-Gordon, Katherine L.; Tull, Matthew T.
Abstract: Despite growing evidence for the efficacy of Gratz and colleagues' emotion regulation group therapy (ERGT) for deliberate self-harm (DSH) among women with borderline personality disorder (BPD), the proposed mechanism of change in this treatment (i.e., emotion regulation) remains largely unexamined. This study examined change in emotion dysregulation as a mediator of the effects of this ERGT on DSH and BPD symptoms, as well as the extent to which change in emotion dysregulation during treatment predicts further improvements in DSH during a 9-month follow-up. Participants included 61 female outpatients with BPD and recent DSH who were randomly assigned to receive this ERGT in addition to their ongoing outpatient therapy immediately ( n = 31) or after 14 weeks ( n = 30). Measures of emotion dysregulation, DSH, and BPD symptoms were administered pre- and post-treatment or -waitlist, and at 9-months post-treatment (for participants in both conditions who received ERGT). Results from a series of mediation analyses provide further support for emotion regulation as a mechanism of change in this treatment. Specifically, results revealed that improvements in emotion dysregulation over the course of treatment mediated the observed reductions in BPD cognitive and affective symptoms during treatment and predicted further improvements in DSH during follow-up. Highlights: Emotion dysregulation is theorized to underlie deliberate self-harm (DSH). Research supports the efficacy of emotion regulation group therapy for DSH in BPD. We examined emotion regulation as the mechanism of change in this ERGT. Reductions in emotion dysregulation mediated the effects of ERGT on BPD symptoms. Reductions in emotion dysregulation predicted improvements in DSH during follow-up.